Cold water immersion recovery protocols: Do they cause cardiac arrhymthmias and represent a cardiovascular risk? - George, K. P.; Dolman, G. M.; Gregson, W.; Somauroo, J.; Jones, H. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In contemporary sporting environments athletes have adopted whole limb cold water immersion (CWI) as a strategy to aid recovery. Little attention has been paid to the cardiovascular risk associated with CWI despite evidence from "work-physiology" studies of substantial numbers of cardiac arrhythmias being induced with water immersion. The aim of this initial study was to evaluate the effect of CWI (8 and 22oC) at rest on heart rate (HR), blood pressure (BP) and cardiac electrical activity (ECG). Methods: Ten healthy male subjects (mean age 25 ± 5; height 1.79 ± 0.04 m; body mass 79.5 ± 4.6 kg) completed two experimental trials consisting of; 30 min supine rest, 10 min CWI and 10 min supine recovery in a stable laboratory environment (22oC, 50% RH). CWI was to the level of the iliac crest and was performed, in a random order, at water temperatures of 8oC and 22oC. HR, BP and both prolonged single lead rhythm and 12 lead ECG data were collected continuously via finger photo-plethysmography, PowerLab and SpaceLabs ECG machines. ECG data were read by a consultant cardiologist. HR and BP were averaged over 1 min intervals across the last 10 min of supine rest, CWI and recovery. Results: HR and mean arterial pressure (MAP) did not significantly changes across the 22oC CWI trial. In the 8oC trial HR increased marginally but MAP was significantly increased during immersion (Rest: 79 ± 7 mmHg; Immersion: 98 ± 12 mmHg, P<0.05) and then returned to baseline during recovery. Sinus arrhythmia and sinus bradycardia were common. There were 2 cases of a low atrial rhythm (1 throughout all phases and another developing in recovery); 1 case with a premature ventricular complex and 2 cases with atrial ectopic beats during baseline or recovery. There was no ST depression but new T-wave inversion in inferior leads occurred in 2 cases during immersion which normalised in recovery. There were no significant time-by-trial interactions for P wave duration and axis, PR duration, QRS duration and axis, QT, QTc, T wave axis and sV1+rV5 voltage. Conclusion: Ten minutes of CWI (at 8oC) resulted in a minor but statistically significant pressor response. Few cardiac arrhythmias were detected and these were not consistently mediated by temperature, trial phase and presented no immediate clinical concern. T wave changes were seen in one athlete, but as to whether this represents a benign phenomenon or an increase in cardiovascular risk is undetermined.